Rebuilding, rebranding, and competitive landscapes: a set-theoretic analysis of authoritarian successor parties. Issue 8 (16th November 2020) - Morse, Yonatan L.
ABSTRACT: This study reevaluates debates over what has allowed authoritarian successor parties (ASPs) to overcome the baggage associated with their past and remain competitive after the Third Wave. Current scholarship points to variation in several factors – the degree to which ASPs can rebuild support using resources from the authoritarian past, the ability of ASPs to rebrand themselves, and the extent to which the new competitive landscape provides electoral opportunities. Yet, there is less consensus over what generalizable conclusions can be drawn. This article departs from former work by presenting the results of a fuzzy-set qualitative comparative analysis (fsQCA) of 46 ASPs. This method is particularly attuned to medium ranges of cases and the notion of causal complexity. I find that there are three distinct causal recipes that produce a competitive ASP: (1) resource advantages and competitive landscapes; (2) resource advantages and self-reform; and (3) mixed legacies and competitive landscapes. The article corrects several standing theories by noting the interaction between causal factors and better accounting for the empirically diverse settings in which ASPs remain competitive.